Scattering Properties of Near-Field Evanescent Wave From Medium With Ellipsoidal and Cylindrical Distributions - Feinan Chen; Jia Li (IEEE Photonics Journal, 2017)
The evolution properties of the near-field evanescent wave scattered from two particles with the ellipsoidal and cylindrical scattering potentials are studied, respectively. Within the accuracy of the first-order Born approximation, the integrations are derived for the scattered fields from these two kinds of particles. It is found that the resultant scattered intensities are closely related to the scattering potential types. Compared with the ellipsoidal particle, the cylindrical one gives rise to less fluctuations of the scattered intensities. It also is shown that the scattered intensity strongly depends on the z-component of the effective radii and summation indices of both particles. Results indicate that the scattered intensity distribution can be tuned by controlling the Effective Radius of Scattering potentials (ERSPs) and summation indices of the medium. The obtained results are useful for determining the structural parameters of tiny particles and molecules by converting the scattering formulas.